KAJIAN TARIF AIR MINUM PDAM DI KABUPATEN LAMANDAU PROVINSI KALIMANTAN TENGAH - Penangsang, Parikesit; Studiviany, Pramita; Santoso, Sigit (JEB17 : Jurnal Ekonomi dan Bisnis, 2020)
In 2017, the achievement of clean drinking water services in Indonesia only reached 72% or the fulfillment was still less than 28%. Hard work is needed to achieve these targets, both through the construction of piping and non-piping networks. The problems faced in the provision of drinking water today include the low coverage of drinking water services. The low operational service coverage is a reflection of the lack of funds for the development of the existing system, inefficient management, or the absence of PDAM administering institutions in the expansion areas or existing UPTD / BLUD institutions that still need improvement from a managerial perspective. The Study on Drinking Water Rates based on Minister of Home Affairs Regulation Number 71 of 2016 concerning Calculation and Determination of Drinking Water Rates, states that drinking water rates are based on restoring operational costs and developing water services. The calculation of the PDAM Water Tariff that has been carried out in PDAM Lamandau Regency is only up to the Basic Cost = Basic Tariff, not yet the Low Tariff and Full Tariff